Antibiotic Therapy for Early Ages and Asthma Development in School Children - Zambrano Ubillus, Roberth; Solorzano Torres, Fanny; Macias Alvia , Aida; Vargas Santos, Jenny (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the research was to determine the association between the use of antibiotics in early ages and the development of asthma at school age. This study is a retrospective observational descriptive approach with a quantitative case-control approach. Medical records of patients from the pediatric area of a Guayaquil hospital were reviewed. The total sample was 366 children. The cases (n = 183) were chosen from the hospital database of children between 5 and 12 years old who have been diagnosed with asthma. Controls were matched in equal numbers and proportions. 43% of the cases used antibiotic therapy before 5 years, with amoxicillin being the most beta-lactamase inhibitor and the most widely used antibiotic (28.8%). The most frequent comorbidity was acute upper respiratory infection (38%). Among the controls, the most used antibiotic corresponded to amoxicillin (34.8%), while the most frequent infection was the same as for the cases (50.0%). An analysis was performed to determine if the difference in distribution concerning the use of antibiotics is significant between cases and controls, and it was determined that there is a much higher percentage of antibiotic use in cases than in controls (60.1% vs. 25.7%; p = 0.011). The analysis reflects an association between the use of antibiotics at an early age and the appearance of asthma at school age. Thus, the use of antibiotics in children under 5 years increases the risk 4.5 times of having asthma at school age.